2022
DOI: 10.1177/10760296221077975
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography for the Prevention of Perioperative Venous Thromboembolism in Orthopedics

Abstract: We have reviewed a large number of relevant literature to determine the deficiencies of orthopedics in the diagnosis and prevention of venous thromboembolism(VTE)events during the perioperative period, and found that the TEG technology has been widely used after liver transplantation, which may make up for the deficiencies. This review expounds the detection principle and latest thromboelastography (TEG) development, and highlights the advantages of TEG over previous screening methods in diagnosing hypercoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…CK MA has previously been used as the primary TEG outcome parameter for CVD risk assessment [28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CK MA has previously been used as the primary TEG outcome parameter for CVD risk assessment [28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombelastography (TEG) is widely used to monitor and direct haemostatic treatment and captures the different aspects of haemostasis from clot initiation to clot lysis [28]. In recent years, it has been demonstrated that TEG can detect prothrombotic haemostatic alterations in populations with high CVD risk compared to controls and may be a useful tool for predicting CVD risk [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…LY30 and LY60 represent the strength of blood clotting at 30 and 60 min after the beginning of fibrinolysis, respectively, reflecting the speed of clot dissolution ( 62 ), despite the no clear variation between LY30 and LY60 in our study. An increase in these values indicates hyperfibrinolysis, while a decrease indicates a weakened fibrinolysis ( 63 ). As discussed above, the controlling and/or regulatory factors of blood hypercoagulability are complex, and our current research found statistical correlations between them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the coagulation function, especially changes in D-dimer levels, were monitored. These factors were beneficial in determining whether a patient would be at high risk of VTE, and whether intervention would help prevent the development of VTE [20][21][22].…”
Section: Discussionmentioning
confidence: 99%